Cadmium trapping by C60 and B-, Si-, and N-doped C60 - Kuganathan, N.; Selvanantharajah, N.; Iyngaran, P.; Abiman, P.; Chroneos, A. (University of Jaffna, 2019)
The removal of heavy metals from the environment has attracted considerable attention as they are toxic and non-biodegradable or destroyable. To minimize their hazard, they should be removed through either physical or chemical capture. Cadmium is a heavy metal that can lead to severe risks to human health. Using the density functional theory with a dispersion correction (DFT + D), we predict the structures and energies of Cd trapped by C60. Furthermore, we substitutionally doped C60 with a single B, Si, and N and examined its trapping behavior. The lowest substitutional energy was calculated for B. Significant enhancement in trapping is observed with B and Si doping outside the surface in particular and our results warrant further experimental investigation